Adaptation, resistance, and access to instructional Technologies : assessing future trends in education - D'Agustino, Steven, 1965- (Hershey Pa. : Information Science Reference, 2011)
'This book captures the current trends in technology integration from PreK-12 to higher education, focusing on the various constituent groups, namely students, teachers, and communities, in education and the effects of educational technology on learning and empowerment'--Provided by publisher
Includes bibliographical references (p. 460-508) and index.
Keywords: Education -- Effect of technological innovations on; Education and State -- United States; Intelligent tutoring systems -- United States; Educational change; Computer-assisted instruction